Hepatoid Adenocarcinoma of the Stomach: A Challenging Diagnostic and Therapeutic Disease through a Case Report and Review of the Literature - Fakhruddin, Najla; Bahmad, Hisham F.; Aridi, Tarek; Yammine, Yara; Mahfouz, Rami; Boulos, Fouad; Awada, Ahmad; Farhat, Fadi (Frontiers in Medicine, 2017)
Hepatoid adenocarcinoma of the stomach (HAS) is a rare aggressive tumor with hepatocellular differentiation. HAS often produces alpha fetoprotein (AFP), and metastasizes to the lymph nodes and the liver. Molecular studies revealed Her2 amplification and overexpression, association with p53 mutations, but no association with KRAS mutations. EGFR and BRAF mutations have not yet been evaluated in hepatoid carcinoma of the stomach so far. Hereby, we present a case of a 41-year-old female patient with hepatoid adenocarcinoma of the stomach with high AFP level and liver metastases. Molecular analysis revealed Her2 overexpression by immunohistochemistry (IHC), but no EGFR, KRAS, or BRAF mutations were detected. The patient underwent chemotherapy type DCX (docetaxel, cisplatinum and capecitabine) every 3 weeks with partial response after 2 cycles, maintained for eight cycles, and then was on maintenance therapy with trastuzumab for seven months before relapsing and dying 18 months from the day of diagnosis. Conclusively, HAS may be misdiagnosed as hepatocellular carcinoma; therefore, it should be considered in the differential diagnosis of multiple hepatic nodules with high alpha fetoprotein, and no history of hepatitis, liver fibrosis or cirrhosis.